The combined effects of alcohol consumption and body mass index on hepatic steatosis in a general population sample of European men and women. Issue 5 (15th January 2015) - Lau, K.; Baumeister, S. E.; Lieb, W.; Meffert, P. J.; Lerch, M. M.; Mayerle, J.; Völzke, H.
Summary Background Research on the association between alcohol consumption and hepatic steatosis revealed conflictive results. Aim To investigate the associations between average daily alcohol consumption and binge drinking with hepatic steatosis, and to analyse combined effects of average daily alcohol consumption and binge drinking with body mass index (BMI) on hepatic steatosis. Methods Data from the population‐based Study of Health in Pomerania (SHIP) conducted in north‐east Germany comprising 4009 adults were used. Alcohol consumption was assessed by self‐report. Serum carbohydrate‐deficient transferrin (CDT) was analysed as biomarker for alcohol consumption. Hepatic steatosis was diagnosed by ultrasonography. Results Analyses revealed a dose–response relationship between average daily alcohol consumption and hepatic steatosis in men starting with a consumption of 20 g of alcohol per day [adjusted odds ratio (OR) compared to abstainers 1.53; 95% confidence interval (CI) 1.15–2.05]. Using CDT as alternative exposure variable confirmed these results. Binge drinking was associated with hepatic steatosis in men (adjusted OR of binge drinkers compared to nonbinge drinkers 1.36, 95% CI 1.06–1.74). The likelihood of having hepatic steatosis increased in men and women with increasing levels of average daily alcohol consumption in combination with overweight or obesity. Similarly, binge drinking in combination with overweight or obesity enhanced the likelihood of having hepatic steatosis. Conclusions Overweight or obesity substantially enhanced the effect of high levels of average daily alcohol consumption and binge drinking on hepatic steatosis in the present study population. This finding underlines the necessity to screen for multiple risk factors in the prevention of hepatic steatosis.